Prevalence of Anaerobic Bacteria in Periodontitis in Relation to Pocket Depth - Suhad Muwafaq Hamdoon; Ghada Younis Abdul-Rahman (University of Mosul, College of Dentistry, 2014)
Aims: : The study evaluated the prevalence of anaerobic bacteria in the subgingival plaque in periodontitis in relation to pocket depth. Materials and Methods :The study was performed on 97 sub-gingival plague sample , pockets depth were measured , anaerobic bacteria were isolated and identified in relation to pockets depth. Results: In this study high prevalence of anaerobic bacteria in the periodontal pockets of patients suffering from periodontitis compared with the gingival sulcus of healthy subjects with marked shifting from mainly Gram positive facultative anaerobic bacteria in shallow pockets to mainly Gram-negative strict anaerobic bacteria in the deep pockets.Conclusion:. Anaerobic culture used in this study provided information about the susceptibility of the individuals to develop periodontal diseases. on bone.